2017
DOI: 10.1080/02699206.2017.1359857
|View full text |Cite
|
Sign up to set email alerts
|

Word-initial rhotic clusters in typically developing children: European Portuguese

Abstract: Rhotic clusters are complex structures segmentally and prosodically and are frequently one of the last structures acquired by Portuguese-speaking children. This paper describes cross-sectional data for word-initial (WI) rhotic tap clusters in typically developing 3-4- and 5-year-olds in Portugal. Additional information is provided on WI /l/ as a singleton and in clusters. A native speaker audio-recorded and transcribed single words in a story-telling task. Results for WI rhotic clusters show an age effect cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
1
7
0
2
Order By: Relevance
“…Tar (2018) took this pattern into account when identifying mismatch patterns in Hungarian child speech, so the actual occurrence of vocalic insertion in children may be somewhat higher. For Bulgarian, epenthesis was reported as a relatively prominent pattern for three-year-olds (Ignatova et al, 2018), and for Portuguese, epenthesis was moderately frequent (around 10%) across the ages 3-5 (Ramalho & Freitas, 2018). Overall for this project, the researchers concluded that "… additional research is needed, particularly with careful measurement of duration of vowel-like elements in both child and adult speech, and careful consideration of quantitative properties of the phenomenon at all ages" (Bernhardt & Stemberger, 2018, p. 570).…”
Section: Vocalic Insertion In Child and Adult Languagementioning
confidence: 97%
See 1 more Smart Citation
“…Tar (2018) took this pattern into account when identifying mismatch patterns in Hungarian child speech, so the actual occurrence of vocalic insertion in children may be somewhat higher. For Bulgarian, epenthesis was reported as a relatively prominent pattern for three-year-olds (Ignatova et al, 2018), and for Portuguese, epenthesis was moderately frequent (around 10%) across the ages 3-5 (Ramalho & Freitas, 2018). Overall for this project, the researchers concluded that "… additional research is needed, particularly with careful measurement of duration of vowel-like elements in both child and adult speech, and careful consideration of quantitative properties of the phenomenon at all ages" (Bernhardt & Stemberger, 2018, p. 570).…”
Section: Vocalic Insertion In Child and Adult Languagementioning
confidence: 97%
“…Bernhardt and Stemberger and collaborators compared the production of word initial liquid clusters in preschoolers aged 3-5 years across several languages: Icelandic (Másdóttir, 2018), Swedish (Lundeborg Hammarström, 2018), Portuguese (Ramalho & Freitas, 2018), Spanish (Perez, Vivar, Bernhardt, Mendoza, Ávila, Carballo, Fresneda, Muñoz & Vergara, 2018), Bulgarian (Ignatova, Bernhardt, Marinova-Todd & Stemberger, 2018), Slovenian (Ozbič, Kogovšek, Stemberger, Bernhardt, Muznik & Novšak Brce, 2018), and Hungarian (Tar, 2018). For most of the languages studied, there was either no evidence of epenthesis as a strategy for cluster production (Swedish, Icelandic) or epenthesis was found to be a relatively infrequent mismatch pattern 1 In the literature, the terms 'epenthesis', 'vowel/vocalic insertion' and 'vowel/vocalic intrusion' are terms used for the phenomenon treated here.…”
Section: Vocalic Insertion In Child and Adult Languagementioning
confidence: 99%
“…Vocalic intrusions in consonant clusters are a property, or prosodic-phonetic bias, of Norwegian ( Garmann et al, 2021 ), as a language with an open transition between the consonants in a cluster ( Endresen, 1991 ). It would be interesting to see whether this phenomenon is treated similarly by parents speaking for example Bulgarian or Portuguese to their children, since children speaking these languages produce vocalic intrusions in clusters ( Ignatova et al, 2018 ; Ramalho and Freitas, 2018 ). This paper has shown how this particular prosodic-phonetic bias is subject to quite detailed and stratified modification in CDS, arguably with multiple functions.…”
Section: Discussionmentioning
confidence: 99%
“…The typical process of phonological acquisition in childhood has been investigated in several languages (Amorin, 2014;Ceron et al, 2017;Kim et al, 2016;Lousada et al, 2012;McIntosh & Dodd, 2008;McLeod & Crowe, 2018;Ramalho & Freitas, 2018;To et al, 2013). There seems to be a universal order of phonological acquisition, whereby stops and nasals are acquired first, followed by fricatives and liquids (Acevedo, 1993;Ceron et al, 2017;Ferrante et al, 2008;Kim et al, 2016;Lousada et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A study (Lousada et al., 2012) that analysed a phonetic‐phonological test for the assessment of articulation and phonological abilities in EP‐speaking children showed that the phonemes /p, b, t, d, k, g, m, n, ɲ, f, v, s, ʃ, x/ were acquired between the ages of 3;0 and 3;5; while /ʃ/ (syllable‐final position), /l, ʎ/ were acquired between 3;6 and 3;11; /z, ʒ, ɾ/ and clusters /pl, kl, fl/ between 4;0 and 4;5; /ɾ/ (syllable‐final position) and clusters /fɾ, vɾ, bɾ, pɾ/ between 4;6 and 4;11; and /ɬ/ (syllable‐final position) and clusters /kɾ, tɾ, dɾ, gɾ/ between 5;0 and 5;5. Clusters are complex structures and frequently among the last to be acquired by Portuguese‐speaking children (Ramalho & Freitas, 2018). Another study (Amorin, 2014) contributed empirical data to the characterization of the final stages of phonological development in EP.…”
Section: Introductionmentioning
confidence: 99%